Machine learning approaches for screening the risk of obstructive sleep apnea in the Taiwan population based on body profile. (2nd October 2022) - Tsai, Cheng-Yu; Liu, Wen-Te; Lin, Yin-Tzu; Lin, Shang-Yang; Houghton, Robert; Hsu, Wen-Hua; Wu, Dean; Lee, Hsin-Chien; Wu, Cheng-Jung; Li, Lok Yee Joyce; Hsu, Shin-Mei; Lo, Chen-Chen; et al.
ABSTRACT: (a) Objective: Obstructive sleep apnea syndrome (OSAS) is typically diagnosed through polysomnography (PSG). However, PSG incurs high medical costs. This study developed new models for screening the risk of moderate-to-severe OSAS (apnea-hypopnea index, AHI ≥15) and severe OSAS (AHI ≥30) in various age groups and sexes by using anthropometric features in the Taiwan population. (b) Participants: Data were derived from 10, 391 northern Taiwan patients who underwent PSG. (c) Methods: Patients' characteristics – namely age, sex, body mass index (BMI), neck circumference, and waist circumference – was obtained. To develop an age- and sex-independent model, various approaches – namely logistic regression, k-nearest neighbor, naive Bayes, random forest (RF), and support vector machine – were trained for four groups based on sex and age (men or women; aged <50 or ≥50 years). Dataset was separated independently (training:70%; validation: 10%; testing: 20%) and Cross-validated grid search was applied for model optimization. Models demonstrating the highest overall accuracy in validation outcomes for the four groups were used to predict the testing dataset. (d) Results: The RF models showed the highest overall accuracy. BMI was the most influential parameter in both types of OSAS severity screening models. (e) Conclusion: The established models can be applied to screen OSAS risk in the Taiwan population and those with similar craniofacial features.